INTERACTION BETWEEN FAMILIES OF CHILDREN WITH SPECIAL NEEDS AND SUPPORT SYSTEM : PARENTAL PERSPECTIVE - Bethere, Dina; Pavitola, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The study analyses the effectiveness of interaction between parents, who bring up children with special needs and the support system. According to the state defined standards and cognitions of scientific research, activities of the support system are considered as qualitative only if they satisfy parents` individual needs of receiving support. The article reflects qualitative research, where parents have naturally been delegated the functions of experts. The results of the study verify the necessity to improve collaborative strategies, employing non-governmental organizations as a resource for promoting collaboration between parents of children with special needs, educational and support institutions.